Analyzing the Application of Speech Act Theory in Editorial Emails of Rejected Manuscripts - Alam, Sohaib; Ajmal, Muhammad; Zeb , Shaista; Mohammed, Bahia Khalifa Ibrahim; Shams, Anam; Rasheed, Tariq (Journal of Education Culture and Society, 2025)
Aim. This paper discusses the use of Speech Act Theory to analyze editorial emails that reject an academic manuscript. The study investigates how the editorial decisions are communicated with different levels of polite, impolite, polite direct and polite assertive language in the analyzed emails' linguistic structure and pragmatic aspects.Methods. Building on the taxonomy of speech acts proposed by John Searle, the study establishes the most common types of speech acts and their roles in rejection communication. The study will establish how editors conduct themselves as they display professionalism while giving negative feedback that could be emotionally uncomfortable to the individuals involved in the work.Results. This research work contributes to the knowledge of pragmatic features in professional discourse to suggest improvements in academic publishing communication practice, and to improve the editor-author relationships.Conclusion. Potential implications of this work include developing better fitting templates for the editorial correspondence that accommodate the communicative purpose and interpersonal relations.